Serum Maresin 1 levels in idiopathic acute anterior uveitis patients - Gül, F. C.; Kobat, S. G.; Kasar, K.; Aydin, S.; Akkoc, R. F. (Masson Editeur, 2022)
Purpose. The purpose of the present study is to assess the levels of Maresin 1 (MaR1) in patients with idiopathic acute anterior uveitis (IAAU) and to compare the MaR1 results with healthy controls. Methods. This study includes 24 patients with idiopathic AAU and 24 healty controls (C). The serum MaR1 levels were analyzed using enzyme -linked immunosorbent assays (ELISA). The erythrocyte sedimentation rate (ESR) and C -reactive protein (CRP) levels were measured at the time of diagnosis. Results. MaR1 levels were statistically significant when the IAAU group was compared with group[ (P9 0.001). When idiopathic MU patients were compared with group C, no statistically significant difference was found between ESR and CRP levels (P=0.086, P=0.549 respectively). Conclusion. Serum MaR1 levels are an important biomarker of disease in patients with idiopathic AAU. (c) 022 Elsevier Masson SAS. All rights reserved.
Niveaux sériques de marésine 1 chez les patients atteints d'uvéite antérieure aiguë idiopathique
Keywords: Maresin; Idiopathic; Uveitis; ESR; CRP